Economic Growth in Southeast Sulawesi: The Pivotal Role of Infrastructure (2010-2022) - Yuyun Anggraini; Sasmita Nabila Syahrir (International Journal of Economics Development Research (IJEDR), 2024)
In recent years, Southeast Sulawesi has witnessed significant infrastructure development, which is expected to stimulate economic growth, attract investments, create job opportunities, and improve its residents' overall quality of life. This study seeks to analyze the effect of infrastructure on the economic growth of Southeast Sulawesi from 2010 to 2022. Utilizing secondary data, including the Gross Regional Domestic Product (GRDP) of Southeast Sulawesi and infrastructure indicators such as roads, water, and electricity, Employing a quantitative approach, specifically Multiple Linear Regression Analysis, this research aims to determine the effect of road, water and electricity infrastructure on economic growth in Sulawesi Tenggara. The findings indicate that when analyzed individually, road and electricity infrastructure significantly influence economic growth. Improved road networks facilitate heightened economic activity by promoting the movement of goods and services, enhancing regional connectivity, and improving accessibility. At the same time, electricity infrastructure proves vital in supporting various sectors and activities, thereby contributing to overall economic growth. Surprisingly, the individual analysis of water infrastructure reveals no significant impact on economic growth, possibly attributed to inefficiencies or ineffectiveness in project implementation or management. However, if the influence of road, water and electricity infrastructure is analyzed simultaneously, the impact is positive and significant on economic growth in Southeast Sulawesi. The synergistic presence of these infrastructure components plays a vital role in supporting economic development. Increasing connectivity, increasing accessibility, and simplifying production and distribution activities contribute to attracting investment, growing competitiveness, and ultimately encouraging the economic development of Southeast Sulawesi as a whole.